The institutional development of the Ministry of Finance and Commerce in the xix century - Morales Ceron, Carlos (2020)
The Ministry of Finance and Commerce (today the Ministry of Economy and Finance (MEF), was the decisive institution that in the 19th century, not only determined the formation of republican finances, but also the formation of the caudillo state. All public expenditure was filtered, and by the voice of its ministers the economic thought of the time was disseminated, always in relation to international markets, in times of boom and crisis, including: Institutional study of the Ministry of Finance and Commerce, the behavior of the republican economy in the nineteenth century, in the context of the governments that in our opinion were the most important, being determinants for the time, analyzed the memories of the main ministers of Finance and Commerce in the governments of San Martin, Simón Bolívar (1821-1826), governments of Ramón Castilla (1845-1862).